Community-based surveillance of unaccompanied and separated children in drought-affected northern Ethiopia - Matthew MacFarlane; Beth L. Rubenstein; Terry Saw; Daniel Mekonnen; Craig Spencer; Lindsay Stark (BMC, 2019)
Abstract Background Children separated from their caregivers in humanitarian emergencies are vulnerable to multiple risks. However, no field-tested methods exist to capture ongoing changes in the frequency and nature of separation in these contexts over the course of a protracted crisis. Methods Recognizing this gap, a mobile phone-based surveillance system was established in a drought-affected district in northern Ethiopia to assess the feasibility of using community focal points to monitor cases of unaccompanied and separated children. A total of 29 focal points were recruited through village elections from 10 villages in the district. Feasibility was assessed directly by measuring the number and quality of messages sent by the focal points each week. The team also evaluated the implementation process and any challenges that arose through observations and key informant interviews with focal points at the conclusion of the project measuring frequency of employing various information gathering techniques, challenges faced, and perceptions of community expectations. Likert scales were used to measure overall satisfaction with the experience of being a focal point, self-assessed difficulty of being a focal point, perceived likelihood of cases captured, and motivation. Results Over a six-month period, the focal points reported 48 cases of separation. The majority of separated children (64.6%) were 10 years of age or older. Work was a major driver of separation, especially for boys. Age, sex, role in community, and density of community had no statistically significant impact on focal point performance in terms of frequency, accuracy, or consistency of messages. The focal points themselves reported high levels of motivation, but suggested several areas for improvement in the surveillance system. Conclusions Without the surveillance system, most of these children would have otherwise been unrecognized. From a technical standpoint the system was successful and resilient in the face of unexpected external challenges. However, focal point participation and accuracy was variable over time and across groups and diminished towards the later months of the study, suggesting that the community-based approach may require additional supports to ensure that the surveillance system is able to accurately capture trends over time.